Variation of the solar cell performance with varying irradiance and temperature in Nigeria - Ike, Chinelo (International Journal of Basic and Applied Sciences, 2014)
In Nigeria sun which is in abundance is the most readily available source of solar energy. It does not contribute to an increase carbondioxide, CO2 and other greenhouse gases in the atmosphere hence non-polluting and requires little or no maintenance. This research work states that solar cells, the basic elements for photovoltaic conversion of solar energy, are especially susceptible to high temperature and irradiation damage primarily due to their large surface. Degradation of electrical and optical characteristics of the solar cells as photo detectors in the increased temperature conditions is one of the most important limitation factors of their application. Since most of the electrical processes in semiconductor devices depend, to some extent, on the temperature, investigations at temperatures higher than room temperature may reveal possible changes in output characteristics of the device. Also the lifetime of the solar PV cell is restricted by the degree of radiation damage that the cell receives. This is an important factor that affects the performance of the solar cell in practical applications. The overall performance of solar cell varies with varying irradiance and temperature. However, both irradiance and temperature affect solar cell efficiency as well as corresponding fill factor also changes. This study gives an idea about how the solar cell performance changes with the change in above mentioned factors in reality and the result is shown by conducting a number experimental.
Keywords: Fill Factor; Irradiance; Irradiation; Temperature.